Women in dramatic place and time : contemporary female characters on stage - Cousin, Geraldine (Routledge, 1996)
Presents detailed analysis of a wide range of plays by British women dramatists from the last two decades. It will be invaluable reading for students of contemporary British theatre, literature and Women's Studies.